Lymphadenopathy, weight loss, and anal lesion in a teenager - Sousa, Jessica; Meira Nisa, Madalena; Coelho, Sónia; Antunes, Joaquina (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Syphilis is a systemic disease with an increasing incidence in adolescents and young adults. Clinical manifestations can be variable and diagnosis requires a high index of suspicion, as syphilis can mimic other systemic diseases. Condylomata lata is a highly infectious manifestation of secondary syphilis, reported in 9-44% of cases. Here is reported the case of an adolescent girl who presented with inguinal lymphadenopathies, urinary and constitutional symptoms, and a history of unprotected sex with her boyfriend, who had been previously diagnosed with a genital ulcer. A complete physical examination was performed, and the detection of an anal lesion raised the hypothesis of perianal condylomata lata as a manifestation of secondary syphilis. All signs and symptoms of infection resolved with treatment. Early detection, appropriate treatment, and prevention of transmission are essential to reduce the burden of the disease.